Psycholinguistics and cognition in language processing - Buga, Duyga, 1991-; Ogeyik, Muhlise Cosgun, 1974- (Information Science Reference, 2018)
"This book provides innovative studies and researches on linguistics, psycholinguistics, neurolinguistics, cognition and related areas. It explores topics such as language and mind, psychology of language, language processing, multilingualism, cognitive linguistics and other multi-disciplined studies and researches related to language"--